Correlación entre algunos parámetros climáticos y la hora del día en Heredia, Costa Rica (ING) - Wright, Jaime (1997)
The present work is an experimental study of the relationship between the local time and global, ultraviolet and infrared radiation, temperature of the air, atmospheric pressure, relative humidity and wind speed at Heredia, Costa Rica (latitude 10° 02’ N, longitude 84° 09’ W, altitude 1050 m) from January 1996 to December 1997. This work will contribute to the development of a model for weather parameters including the time of the day. Correlation between weather variables and the month of the year was elaborated in earlier work. Regression analysis between mean monthly hourly weather data and local time yield a cubic relation as the best fit. Experimental observations presented in this work are consistent with atmospheric physical processes.